2020
DOI: 10.1002/bit.27301
|View full text |Cite
|
Sign up to set email alerts
|

Selecting for lactic acid producing and utilising bacteria in anaerobic enrichment cultures

Abstract: Lactic acid‐producing bacteria are important in many fermentations, such as the production of biobased plastics. Insight in the competitive advantage of lactic acid bacteria over other fermentative bacteria in a mixed culture enables ecology‐based process design and can aid the development of sustainable and energy‐efficient bioprocesses. Here we demonstrate the enrichment of lactic acid bacteria in a controlled sequencing batch bioreactor environment using a glucose‐based medium supplemented with peptides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 58 publications
(68 reference statements)
0
18
1
Order By: Relevance
“…We also found that the genus of Bifidobacterium (Bifidobacteriaceae of phylum Actinobacteria) was overrepresented in lactating females of Tibetan macaques. As important probiotics, members of Bifidobacterium could produce short-chain fatty acids (SCFAs) including lactic, acetic, propionic, and butyric acid [ 46 ], which may benefit the lactating Tibetan macaques’ health, such as biological barrier, nutrition, immune enhancement and improvement of gut function [ 47 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 98%
“…We also found that the genus of Bifidobacterium (Bifidobacteriaceae of phylum Actinobacteria) was overrepresented in lactating females of Tibetan macaques. As important probiotics, members of Bifidobacterium could produce short-chain fatty acids (SCFAs) including lactic, acetic, propionic, and butyric acid [ 46 ], which may benefit the lactating Tibetan macaques’ health, such as biological barrier, nutrition, immune enhancement and improvement of gut function [ 47 , 48 , 49 ].…”
Section: Discussioncontrasting
confidence: 98%
“…Sucrose is a disaccharide composed of glucose (hexose) and fructose (pentose) which theoretically provides equal conditions for the growth of both groups of bacteria. However, other studies revealed that LAB display both a higher growth rate and a higher ability of substrate uptake than Clostridia which allows them to out-compete other fermentative bacteria [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Both SBR and chemostat systems have been used as a tool for studying mixed culture physiology and for creating a selective pressure toward certain characteristics ( Temudo et al, 2007 , 2009 ; Stouten et al, 2019 ; Rombouts et al, 2020 ). In the absence of storage polymers, SBR cultivation leads to a selective pressure on growth rate, whereas chemostat cultivation selects for substrate affinity.…”
Section: Discussionmentioning
confidence: 99%